Literature Review: Information Technology in Early Detection of Pregnancy Risks and Stunting Prevention in the Era of the COVID-19 Pandemic - Heni Puji Wahyuningsih (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2021)
The competence of midwives in early detection of pregnancy risk and prevention of stunting is an important factor to improve health status. The competence of midwives contributes to the improvement of maternal health status by 79%. In addition to the ability of midwives, the independence of pregnant women is also needed in improving the quality of life of children. In the era of the pandemic, access to information is increasingly limited, so it is necessary to develop information technology that is easily accessible by all groups. The purpose of this article is obtaining a theoretical study of information to improve the competence of midwives and obtaining a theoretical study of information technology to increase the independence of pregnant women in early detection of pregnancy risk and stunting prevention. The design used is a literature review. Articles are collected using search engines such as EBSCO, Science direct, and Proquest. The criteria for the articles used are those published from 2015 to 2021. Based on the articles collected, the results show that Utilization of information technology can be used for various things. The target of information technology can penetrate various circles. The need for information technology today is unavoidable and must be improved. Website-based application is one of the information technology that can be accessed by anyone who has the internet and its use is easy. The conclusion of the study is that information technology can be used in early detection of pregnancy risk and stunting prevention.